Intrasplenic Arterial Aneurysms during Pregnancy - Mahmoud M. S. Abu-khalaf; Sokiyna M. Al-Ameer; Moath M. Smadi; Ayman Qatawneh; Osama A. Smara; Azmy T. Hadidy (Case Reports in Obstetrics and Gynecology)
Splenic artery aneurysms account for about 60% of all visceral aneurysms. Pregnancy is a risk factor for splenic artery aneurysms rupture with high maternal mortality and fetal loss. Intrasplenic arterial aneurysms are extremely rare and have not been reported to be associated with pregnancy. This report presents a 34-year-old woman during the second trimester, admitted with severe left upper quadrant and left shoulder pain. She had two uncomplicated intrasplenic aneurysms. Splenectomy was done. She delivered a full term healthy girl. This is the first report of acute abdomen during pregnancy caused by intrasplenic artery aneurysms with maternal and fetal survival.